Neuroprotective effects of cutamesine, a ligand of the sigma‐1 receptor chaperone, against noise‐induced hearing loss. Issue 5 (22nd January 2015) - Yamashita, Daisuke; Sun, Guang‐wei; Cui, Yong; Mita, Shiro; Otsuki, Naoki; Kanzaki, Sho; Nibu, Ken‐ichi; Ogawa, Kaoru; Matsunaga, Tatsuo
Abstract : The sigma‐1 receptor, which is expressed throughout the brain, provides physiological benefits that include higher brain function. The sigma‐1 receptor functions as a chaperone in the endoplasmic reticulum and may control cell death and regeneration within the central nervous system. Cutamesine (1‐(3, 4‐dimethoxyphenethyl)−4‐(3‐phenylpropyl) piperazine dihydrochloride) is a ligand selective for this receptor and may mediate neuroprotective effects in the context of neurodegenerative disease. We therefore assessed whether cutamesine protects the inner ear from noise‐induced or aging‐associated hearing loss. Immunohistochemistry and Western blotting revealed that the sigma‐1 receptor is present in adult cochlea. We treated mice with 0, 3, or 30 mg/kg cutamesine from 10 days before noise exposure until the end of the study. All subjects were exposed to a 120‐dB, 4‐kHz octave‐band noise for 2 hr. We assessed auditory thresholds by measuring the auditory‐evoked brainstem responses at 4, 8, and 16 kHz, prior to and 1 week, 1 month, or 3 months following noise exposure. For the aging study, measurements were made before treatment was initiated and after 3 or 9 months of cutamesine treatment. Damage to fibrocytes within the cochlear spiral limbus was assessed by quantitative histology. Cutamesine significantly reduced threshold shifts and cell death within the spiral limbus in response to intense noise. These effects were not dose or time dependent. Conversely, cutamesine did not prevent aging‐associated hearing loss. These results suggest that cutamesine reduces noise‐induced hearing loss and cochlear damage during the acute phase that follows exposure to an intense noise. © 2015 Wiley Periodicals, Inc.